Early nociceptive evoked potentials in symptomatic and asymptomatic transthyretin mutation carriers - Massucco, Sara; Bruzzone, Viola; Marinelli, Lucio; Stara, Silvia; Mandich, Paola; Venturi, Consuelo; Gemelli, Chiara; Schenone, Angelo; Leandri, Massimo; Grandis, Marina (Frontiers in Neurology, 2025)
IntroductionSmall fiber involvement is an early feature of hereditary transthyretin amyloidosis with polyneuropathy (ATTRv-PN), but neurophysiological assessment remains challenging due to the lack of reliable methods. Nociceptive evoked potentials (NEPs), recently introduced to evaluate the nociceptive pathway, were employed here to identify potential neurophysiological abnormalities in ATTRv-PN.MethodsFourteen transthyretin mutation carriers (eight ATTRv-PN, six asymptomatic) underwent a cross-sectional evaluation, including clinical scales, NEPs, pain-related evoked potentials (PREPs), somatosensory evoked potentials, electrochemical skin conductance, and skin biopsy. Evoked potentials were compared with 14 age-matched healthy controls.ResultsNEPs were abnormal in 75% of ATTRv-PN patients and 50% of asymptomatic carriers, either absent or delayed. In contrast, PREPs were impaired in only 37.5% of ATTRv-PN patients and none of the asymptomatic carriers. All but two ATTRv-PN patients, and none of the asymptomatic carriers, showed reduced electrochemical skin conductance at the palms and soles.DiscussionNEPs appear valuable for assessing small fiber impairment in ATTRv-PN. They may enable early detection of disease onset in asymptomatic carriers and provide a means to monitor disease progression in ATTRv-PN.